Utilization and Expenditures Trends of Phytopharmaceuticals in Indonesia: Strategic Approaches to Boost Herbal Product Competitiveness - Diara Oktania; Dumilah Ayuningtyas; Yeni; Pujiyanto (JURNAL KESMAS DAN GIZI (JKG), 2026)
Traditional medicine in Indonesia, rooted in local wisdom, is recognized nationally and internationally to support public health preventively, promotively, and curatively, backed by government commitments through regulations such as jamu certification and the Germas program, as well as the abundant biodiversity of thousands of medicinal plant species serving as raw materials for the significant national traditional medicine industry, with ongoing scientification efforts to ensure safety and efficacy. This study aimed to identify trends in the utilization and expenditure of phytopharmaceutical drugs and to provide alternative strategies for enhancing the competitiveness of phytopharmaceuticals as traditional medicine. A cross-sectional study with a quantitative descriptive approach utilized secondary data on domestic phytopharmaceutical drug expenditures from 2023–2024 sourced from the Ministry of Health's LKPP e-purchasing system, which was processed using Microsoft Excel and analyzed descriptively for frequency distribution, percentages, patterns, and trends. Total phytopharmaceutical expenditure reaches Rp25.94 billion, with an increase from Rp11.08 billion in 2023 to Rp14.86 billion in 2024; provinces with the highest spending include Central Java (Rp3.88 billion), followed by West Java (Rp3.02 billion) and East Java (Rp2.38 billion), which contribute more than one-third of the national total, while immunomodulator products like Stimuno dominate with Rp15.01 billion, but utilization for chronic diseases remains low, such as hypertension (Tensigard: Rp1.08 billion) and diabetes (Diabadex: Rp0.295 billion). This study concludes that although phytopharmaceutical expenditure and utilization show positive trends, their utilization is not yet optimal due to limitations in integration into the National Health Insurance, regional distribution disparities, high research costs, as well as low promotion and acceptance among healthcare professionals and the public.